Antimicrobial and physical-mechanical properties of pectin/papaya puree/cinnamaldehyde nanoemulsion edible composite films - Otoni, Caio G.; Moura, Marcia R. de [UNESP]; Aouada, Fauze A. [UNESP]; Camilloto, Geany P.; Cruz, Renato S.; Lorevice, Marcos V.; Soares, Nilda de F. F.; Mattoso, Luiz H. C. (Elsevier B.V., 2014)
The rising demand for bio-based materials to be used in food packaging has encouraged the development of novel, environmentally-friendly films. Fruit puree has the potential to be incorporated in the film-forming solution so that to produce edible films. The major components of plant essential oils (e.g., cinnamaldehyde) deliver antimicrobial properties against food pathogens and may be released by active films in an effort to replace synthetic preservatives. This work aimed at producing cinnamaldehyde nanoemulsions of different droplet sizes, as well as assessing the effect of papaya puree and cinnamaldehyde droplet diameter in the antimicrobial and physical-mechanical properties of high or low methylester pectin films. Increased stirring energies reduced droplet diameter. Papaya puree reduced films' resistance and rigidity while increased extensibility and water vapor permeability. Cinnamaldehyde nanoemulsions balanced the plasticizing effect of papaya puree by increasing rigidity and decreasing extensibility and permeability to water vapor of pectin films. Also, cinnamaldehyde provided antimicrobial properties against Escherichia coli, Salmonella enterica, Listeria monocytogenes, and Staphylococcus aureus. The reduction on droplet diameter did not influence the physical-mechanical properties of the films, but remarkably improved bacterial inhibition due to the higher delivery of active compounds having increased surface areas. Antimicrobial edible films from renewable sources were successfully produced here, and the improved bacterial inhibition provided by the same cinnamaldehyde content with smaller nanodroplets may play an important role in reducing preservative content as required by consumers. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Active packaging; Pectin; Papaya puree; Cinnamaldehyde; Nanoemulsions; Antimicrobial properties